2018
DOI: 10.3389/fpls.2018.00920
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Macrophomina phaseolina (Fungus) Resistant and Glufosinate (Herbicide) Tolerant Transgenic Jute

Abstract: The worldwide demand for natural bast fibers is met aptly by the long, golden and silky fibers of jute. This highest bast fiber producing crop is of great applicability and is extensively used in paper and textile industry. Macrophomina phaseolina (Tassi) Goid is a severely devastating necrotrophic fungal pathogen causing stem rot, root rot, and charcoal rot diseases in both the cultivated species of jute – Corchorus capsularis and Corchorus olitorius. Another major problem faced in jute cultivation is profuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Thus, genetic engineering needs to be employed for developing plants with improved Macrophomina resistance. The Chill1 gene from Oryza sativa confers Macrophomina tolerance in transgenic Corchorus olitorius (Majumder et al 2018). Earlier, our group has shown the involvement of JcPR-10a gene from Jatropha curcas towards reducing M. phaseolina susceptibility via its RNase activity and cytokinin binding potential (Agarwal et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, genetic engineering needs to be employed for developing plants with improved Macrophomina resistance. The Chill1 gene from Oryza sativa confers Macrophomina tolerance in transgenic Corchorus olitorius (Majumder et al 2018). Earlier, our group has shown the involvement of JcPR-10a gene from Jatropha curcas towards reducing M. phaseolina susceptibility via its RNase activity and cytokinin binding potential (Agarwal et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…plants was carried out to analyze their herbicide resistance potential. It was found that control plants died after 12 h of glufosinate spray (0.25%) while transgenic plants successfully recovered from herbicide stress after 7th day of spray 44 . Our results of herbicide tolerance assay are in consonance with these reports.…”
Section: Residual Phytotoxic Effectmentioning
confidence: 99%
“…The seed-borne fungal disease e.g. stem-rot caused by Macrophomina phaseolina (Tassi) Goid and black-band caused by Botryodiplodia theobromae are often transmitted through jute seeds [13,14]. Corchorus olitorius appeared immune to the anthracnose disease caused by Colletotrichum corchori [15].…”
Section: Introductionmentioning
confidence: 99%